Impact of culturing conditions on the abundance and composition of long chain alkyl diols in species of the genus Nannochloropsis. (June 2017) - Balzano, Sergio; Villanueva, Laura; de Bar, Marijke; Sinninghe Damsté, Jaap S.; Schouten, Stefan
Graphical abstract: Nannochloropsis species contain lipids with a C28 –C32 alkane carbon skeleton with one terminal and one mid-chain (13–15) functional group; their abundance under different culturing conditions was investigated and found to be remarkably stable. Highlights: We investigated long chain alkyl diol (LCD) abundance in Nannochloropsis spp. LCD abundances are stable during growth and under different culturing conditions. LCDs are likely to play a protective role in Nannochloropsis cells wall. LCDs concentrations in seawater and freshwater may reflect algal abundance. Abstract: Long chain alkyl diols (LCDs) are widespread in sediments and are synthesized, among others, by microalgae of the genus Nannochloropsis . The factors regulating the synthesis of LCDs and their biological function are, however, unclear. We investigated the changes in abundance of free + ester-bound LCDs, extracted by saponification and acid hydrolysis, during the growth of three Nannochloropsis species and incubated the species having the highest LCD abundance ( Nannochloropsis oceanica ) under different conditions known to affect the fatty acid content (i.e. light irradiance, salinity, nitrogen depletion, desiccation, cold shock) in order to evaluate their impact on LCD production. LCD abundances were relatively stable suggesting that they are not used as storage lipids, and supporting the assumption that LCDs are building blocks of an aliphatic biopolymer located in the outer cell wall (algaenan). Oxidative stress caused by hydrogen peroxide led to a decrease in the C32:1 diol, as well as other algaenan-associated compounds such as 15-OH-C32:0 fatty acid and C32:2 alkenol suggesting that algaenans can play a role in the protection of Nannochloropsis cells. The relatively constant amount of LCDs per cell suggests that the abundance of LCDs in aquatic environments may be used as an indicator for the abundance of diol-producing algae. Interestingly, the abundance of C30:0 13-hydroxy and C32:0 15-hydroxy fatty acids, potential precursors for LCDs, correlate with those of the major C14:0 and C16:0 fatty acids. This supports the idea that the biosynthesis of LCHFAs might proceed by hydroxylation and elongation of shorter C14 –C16 fatty acids.